ẢNH HƯỞNG CỦA pH, NHIỆT ĐỘ VÀ MỘT SỐ ION KIM LOẠI TỚI HIỆU QUẢ LOẠI BỎ PHẨM NHUỘM REACTIVE BLUE 161 CI BẰNG PHẢN ỨNG FENTON - Đức, Đào Sỹ; Hồng Nhung, Đỗ Thị (Vietnam Journal of Chemistry, 2012)
In this study, one of the advanced oxidation processes, the reaction between iron (II) sulfate and hydrogen peroxide (Fenton reaction) was applied for the degradation of Reactive Blue 161 (RB 161 CI). The effect of pH, temperature and several metal ions (Mn2+, Cu2+, Fe2+) on the treatment efficiencies were investigated. The results showed that the optimum conditions of pH, temperature were 3 and 35oC, respectively; the activation energy of the Fenton reaction for the degradation of RB 161 CI was approximately 34.95 kJ.mol-1. These metal ions have strong effects on the treatment efficiencies.  The treatment efficiencies decrease in the following order: Fe2+ (as FeSO4. 7H2O) > Cu2+ > Fe2+ (as Mohr salt) > Mn2+. At the suitable conditions, more than 90% of RB 161 CI were removed. Keywords: Advanced oxidation process; RB 161 CI; Fenton reaction; Textile wastewater.